U.S. monetary-fiscal regime changes in the presence of endogenous feedback in policy rules - Yoosoon Chang; Boreum Kwak (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2017)
We investigate U.S. monetary and fiscal policy regime interactions in a model, where regimes are determined by latent autoregressive policy factors with endogenous feedback. Policy regimes interact strongly: Shocks that switch one policy from active to passive tend to induce the other policy to switch from passive to active, consistently with existence of a unique equilibrium, though both policies are active and government debt grows rapidly in some periods. We observe relatively strong interactions between monetary and fiscal policy regimes after the recent financial crisis. Finally, latent policy regime factors exhibit patterns of correlation with macroeconomic time series, suggesting that policy regime change is endogenous.
Additional information: A completely revised version of this paper has been published as Chang, Yoosoon; Kwak, Boreum; Qiu, Shi: U.S. Monetary and Fiscal Policy Regime Changes and Their Interactions. IWH Discussion Paper 12/2021. Halle (Saale) 2021: https://hdl.handle.net/10419/247268; More recent version: https://hdl.handle.net/10419/247268
Keywords: C13; C32; C38; E52; E58; E63; 330; monetary and fiscal policy interactions; endogenous regime switching; adaptive LASSO; time-varying coefficient VAR; factor augmented VAR